A devil and her love song. Volume 7 - Tōmori, Miyoshi; MacFarlane, Ysabet Reinhardt (Viz Media, 2013)
"As Maria begins to recall bits and pieces of her tragic past, Yusuke tells her that he'll stay by her side and support her, no matter what. Meanwhile, Maria still hopes to reconcile with Anna, so she enrolls in the same music school that Anna attends. Unfortunately, it doesn't seem like Anna wants Maria's help or friendship" -- from publisher's web site.